Evaluation of Risk and Prognosis Factors of Acute Kidney Injury in Patients With HELLP Syndrome During Pregnancy - Wang, Lijuan; Tang, Dongjie; Zhao, Haijun; Lian, Mingfeng (Frontiers in Physiology, 2021)
Hemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome complicated with acute renal failure (AKI) is an important cause of maternal mortality and morbidity. The present retrospective study aims to identify risk and prognosis factors that are associated with AKI in patients with HELLP syndrome during pregnancy. A total of 110 pregnant HELLP patients with or without AKI from an 8-year period were studied. 65 of the patients were diagnosed with AKI based on the Kidney Disease Outcomes Quality Initiative (KDOQI) criteria. Levels of the lowest hemoglobin and serum creatinine and bleeding were identified as independent risk factors for AKI onset. Infection serum creatinine level were identified as independent risk factors for maternal mortality. In addition, we also found that these factors were significantly different in AKI patients of different severity. The overall complete recovery rate was 75.5% (83 out of 110), with no difference between the AKI and non-AKI groups. The overall death rate was 4.5% (5 out of 110), where 1 of the patient was from the non-AKI group and the other 4 were from the AKI group. Our results provide valuable indications for clinical doctors during their diagnosis, treatment and monitoring of recovery status in HELLP patients complicated with AKI.